Natural Resources Based Green Trade Model for Green Growth in Brazil, Russia, Indonesia, Singapore, India and China (BRISIC) - Lola Irmayunda; Bakhtiar Efendi; Wahyu Indah Sari; Rusiadi Rusiadi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Researchers in this study aim to determine the Natural Resources-Based Green Trade Model for Green Growth in Brazil, Russia, Indonesia, Singapore, India and China (BRISIC). The method in this research is using the ARDL Panel method. The variables used in this research are Green Growth, Green Trade, Natural Resources, Financial Inclusion, Green Innovation, Digital Economy. The results of this research are from the Green Trade Model Based on Natural Resources on Green Growth in Brazil, Russia, Indonesia, Singapore, India and China (BRISIC) using the panel method, it can be concluded that in BRISIC countries the variable that has an overall influence is green trade. and Natural resources both Short Run Equation and Long Run Equation.